Development of a synergetic research environment for modeling complex productive and economic systems - Klachek, Pavel М; Polypan, Kseniia L; Liberman, Irina V (St. Petersburg State Polytechnical University Journal. Economics, 2019)
The paper deals with the problems associated with the development of modern computer technology decision-making in the digital economy, as well as methods, algorithms and software for solving control problems and decision-making in socio-economic production systems. The authors of the article propose a promising approach, having an interdisciplinary character, located on the border of the following areas: hybrid intelligent systems, synergistic artificial intelligence, neuro and psychophysiology, philosophy, cybernetics, economic and mathematical modeling, etc. Three laws of synergistic hybrid computational intelligence of complex, poorly formalized, multicomponent production and economic systems (SMPES) are considered: mutual adaptation, discrete series of structures and the law of transformations. A two-level model of the synergistic hybrid computational intelligence of the SMPES is presented, on the basis of which the evolutionary model of the synergistic hybrid computational intelligence of the SMPES is formulated. A model of the synergistic research environment of the SMPES based on hybrid computational models is considered. The architecture of the applied instrumental environment of "soft" mathematical modeling of SMPES is presented. The basics of creating a 5d technology platform for designing intelligent high-tech systems, enterprises and industries are presented, the main advantage of which is the use of a universal information platform in the form of a hybrid intelligent decision-making support system that quickly transforms into a specific system, specific subject area ( mechanical engineering, heavy metallurgy, oil and gas, etc.), allowing you to add new quality to decision-making processes, as well as to ensure the creation and wide effective use of new knowledge, both for individual enterprises and entire industries, innovation clusters and zones. Based on the instrumental environment of "soft" mathematical modeling of SMPES and 5d technology-platform design of intelligent high-tech systems, enterprises and industries, the authors developed, patented and successfully implemented a set of applied tools for the development of key socio-economic sectors of the regions of the Russian Federation. The proposed methods, models and applied tools allowed the team to begin creating a universal, unparalleled in the world technology for the synthesis of innovative developments, products and high-tech services, obtained through the integration of various methods and applied tools and the subsequent generation of specialized technological chains and production and economic new generation systems.